2022
DOI: 10.1007/s10055-022-00660-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy study of the Oculus Touch v2 versus inertial sensor for a single-axis rotation simulating the elbow’s range of motion

Abstract: Virtual reality (VR) has emerged as a valid addition to conventional therapy in rehabilitation and sports medicine. This has enabled the development of novel and affordable rehabilitation strategies. However, before VR devices can be used in these situations, they must accurately capture the range of motion of the body-segment where they are mounted. This study aims to state the accuracy of the Oculus Touch v2 controller when used to measure the elbow’s motion in the sagittal plane. The controller is benchmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…In contrast to previous studies, Rojo et al [71] found a high agreement level of 0.999 (with a 95% confidence interval) between measurements of forearm flexion-extension using both Oculus Touch v2 controllers and IMU devices. However, the controllers exhibit inaccuracies, especially near a 90 • angle in the sagittal rotation plane.…”
Section: Reliability Technical Features and Limitations Of Hmd-vrcontrasting
confidence: 76%
See 4 more Smart Citations
“…In contrast to previous studies, Rojo et al [71] found a high agreement level of 0.999 (with a 95% confidence interval) between measurements of forearm flexion-extension using both Oculus Touch v2 controllers and IMU devices. However, the controllers exhibit inaccuracies, especially near a 90 • angle in the sagittal rotation plane.…”
Section: Reliability Technical Features and Limitations Of Hmd-vrcontrasting
confidence: 76%
“…Despite this, they adequately capture the full range of motion of the elbow joint in virtual environments. According to the authors [ 71 ], while minor misalignments may be acceptable in VR applications where precision is not critical, for tasks requiring high accuracy in orientation measurement, an IMU sensor is preferable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations